Impactos técnicos de alta penetración de fernc en un sistema de transmisión (2020)
This degree project analyzes the technical impacts that occur in a transmission system due to a high percentage of integration of non-conventional renewable energy sources (RES) such as wind and photovoltaic solar energy. The IEEE RTS 24-node system was considered as a test transmission system, in which the technical impacts on the steady state, the short-circuit level and the transient stability were evaluated considering aggregate models of wind and photovoltaic parks in different case studies. In each of these cases, different generation and demand scenarios were analyzed in the winter and summer seasons. In Case 1, coal-based generators were replaced by photovoltaic and wind sources so that, in total, the penetration of RES generation represented around 30% of the installed capacity of the system. In Case 2-A, an expansion was made in the capacity of the solar and wind plants installed in Case 1. In Case 2-B, the coal generators were replaced only by the wind sources considered in the Case 1 and the capacity of the system was expanded by 538MW of photovoltaic generation. Regarding the studies carried out, in stable state, as an operation criterion, it was verified if the voltage of all the buses of the system was between 0.95 and 1.05 p.u. and that no line or transformer is overloaded. In short-circuit condition, photovoltaic and wind farms with type III and IV turbines were modeled as Norton equivalents, taking the recent literature as a reference. From this model, the short-circuit level was evaluated by causing a three-phase and single-phase fault in the 24 nodes of the system for each scenario. Finally, the ability of the system to return to a stable state when subjected to a disturbance was evaluated through a study of transient and dynamic stability.